Depression Symptoms and Inflammation in Chronic Functional Constipation Patients - Hamzah Shatri; Edward Faisal; Murdani Abdullah; Ari Fahrial Syam; Amanda Pitarini Utari; Virly Nanda Muzellina; Saskia Aziza Nursyirwan; Aly Lamuri (Acta Medica Indonesiana, 2023)
Background: Inflammation in chronic functional constipation (CFC) occurs systemically and has association with depressive symptoms. Biomarkers of inflammation can be assessed by the neutrophil to lymphocyte ratio and platelet to lymphocyte ratio. These inflammation biomarkers are stable, cheap, and widely available. This study aimed to determine the profile and the correlations between depressive symptoms and inflammation in CFC patients. Methods: This cross-sectional study involved subjects aged 18-59 years with chronic functional constipation. We use validated Beck Depression Inventory-II (BDI-II) to assess depressive symptoms. We collected the data regarding complete peripheral blood examination, liver function, kidney function, electrolytes, and neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR). Bivariate analysis with Chi-Square test for categorical data and t-test or ANOVA test for numerical data. Multivariate analysis used logistic regression to look at risk factors for depression with p < 0.05 as a statistical significant level. Results: A total of 73 subjects with CFC were recruited with a mean age is 40.2 years, mostly women and working as housewives. Proportion of depressive symptoms in CFC patients was 73.0%, including mild depression 16.4%, moderate depression 17.8%, and severe depression (28.8%). The mean NLR in non-depressive subjects was 1.8 (SD 0.7), while in depressive subjects was 1.94 (SD 0.1) (p>0.05). The mean NLR in mild depression subjects was 2.2 (SD 1.7), in moderate depression was 2.0 (SD 0.7), and in severe depression was 1.9 (SD 0.5) (p>0.05). The mean PLR in non-depressive subjects was 134.3 (SD 0.1), whereas in depressive subjects it was 138.9 (SD 46.0) (p>0.05). The mean PLR in mild depression subjects was 142.9 (SD 60.6), in moderate depression was 135.4 (SD 41.2), and in major depression was 139.0 (SD 37.1) (p>0.05). Conclusion: This study found that CFC patients were middle-aged, mostly women and working as a housewife. In general, biomarkers of inflammation were found to be higher in depressive subjects than non-depressive subjects, although not statistically significant.